Method for manufacture and cryopreservation of cartilage microtissues - Md. Shafiullah Shajib; Kathryn Futrega; Rose Ann G Franco; Eamonn McKenna; Bianca Guillesser; Travis J Klein; Ross W Crawford; Michael R Doran (Journal of Tissue Engineering, 2023)
The financial viability of a cell and tissue-engineered therapy may depend on the compatibility of the therapy with mass production and cryopreservation. Herein, we developed a method for the mass production and cryopreservation of 3D cartilage microtissues. Cartilage microtissues were assembled from either 5000 human bone marrow-derived stromal cells (BMSC) or 5000 human articular chondrocytes (ACh) each using a customized microwell platform (the Microwell-mesh). Microtissues rapidly accumulate homogenous cartilage-like extracellular matrix (ECM), making them potentially useful building blocks for cartilage defect repair. Cartilage microtissues were cultured for 5 or 10 days and then cryopreserved in 90% serum plus 10% dimethylsulfoxide (DMSO) or commercial serum-free cryopreservation media. Cell viability was maximized during thawing by incremental dilution of serum to reduce oncotic shock, followed by washing and further culture in serum-free medium. When assessed with live/dead viability dyes, thawed microtissues demonstrated high viability but reduced immediate metabolic activity relative to unfrozen control microtissues. To further assess the functionality of the freeze-thawed microtissues, their capacity to amalgamate into a continuous tissue was assess over a 14 day culture. The amalgamation of microtissues cultured for 5 days was superior to those that had been cultured for 10 days. Critically, the capacity of cryopreserved microtissues to amalgamate into a continuous tissue in a subsequent 14-day culture was not compromised, suggesting that cryopreserved microtissues could amalgamate within a cartilage defect site. The quality ECM was superior when amalgamation was performed in a 2% O 2 atmosphere than a 20% O 2 atmosphere, suggesting that this process may benefit from the limited oxygen microenvironment within a joint. In summary, cryopreservation of cartilage microtissues is a viable option, and this manipulation can be performed without compromising tissue function.